“Does Experience of Distributor Has Moderating Effect on The Mediating Factors Affecting the Performance of Mutual Fund Distributors? - et. al., Dr. Viral Bhatt , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to find out that does fund distributors experience in the field of mutual fund has a vital importance? And if so, how does the experience of distributors have any effect on the performance of mutual fund. The structured questionnaire has been administered to 1007 respondents. Experience being the categorical moderator is been study in this research. The moderating and mediating effect of experience is been studied in this paper specifically on Indian Mutual fund Industry. The results showed very interesting facts about the overall direct and mediating impact of factors and the moderating effect of experience.